The Relationship Between Early Maladaptive Schemas, Attachment Quality, and Depression Symptoms in Adolescents - Tahaei, Seyed Yasin; Sayad Arbabi, Zahra (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: The aim of this study was to examine the relationship between early maladaptive schemas, attachment quality, and depressive symptoms in adolescents in Tehran.Methods and Materials: This descriptive-correlational study was conducted on 385 adolescents aged 13 to 18 years in Tehran, selected through convenience sampling. Data were collected using the Beck Depression Inventory-II, the Young Schema Questionnaire-Short Form, and the Experiences in Close Relationships Questionnaire. Data analysis was performed using Pearson correlation and multiple regression analysis with SPSS-27.Findings: Pearson correlation results indicated a significant negative correlation between attachment quality and depressive symptoms (r = -0.46, p < 0.01), and a significant positive correlation between all domains of early maladaptive schemas and depression (highest for disconnection and rejection, r = 0.51, p < 0.01). Linear regression analysis revealed that attachment quality and five domains of early maladaptive schemas collectively explained 37% of the variance in depressive symptoms (R² = 0.37, F(6, 378) = 35.14, p < 0.01).Conclusion: These findings suggest that both attachment quality and the intensity of early maladaptive schemas play crucial roles in predicting depressive symptoms in adolescents, highlighting the importance of addressing these factors in preventive and therapeutic interventions.